Small Bowel Injury in Peritoneal Encapsulation following Penetrating Abdominal Trauma - K. Naidoo; S. Mewa Kinoo; B. Singh (Case Reports in Surgery)
Small bowel encapsulation is a rare entity which is usually found incidentally at autopsy. We report the first case of peritoneal encapsulation encountered serendipitously at laparotomy undertaken for penetrating abdominal trauma and review the literature on peritoneal encapsulation. We also compare this phenomenon to abdominal cocoon and sclerosing encapsulating peritonitis.